Plasma protein binding: From discovery to development. Issue 9 (24th June 2013) - Bohnert, Tonika; Gan, Liang‐Shang; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract The importance of plasma protein binding (PPB) in modulating the effective drug concentration at pharmacological target sites has been the topic of significant discussion and debate amongst drug development groups over the past few decades. Free drug theory, which states that in absence of energy‐dependent processes, after steady state equilibrium has been attained, free drug concentration in plasma is equal to free drug concentration at the pharmacologic target receptor(s) in tissues, has been used to explain pharmacokinetics/pharmacodynamics relationships in a large number of cases. Any sudden increase in free concentration of a drug could potentially cause toxicity and may need dose adjustment. Free drug concentration is also helpful to estimate the effective concentration of drugs that potentially can precipitate metabolism (or transporter)‐related drug–drug interactions. Disease models are extensively validated in animals to progress a compound into development. Unbound drug concentration, and therefore PPB information across species is very informative in establishing safety margins and guiding selection of First in Human (FIH) dose and human efficacious dose. The scope of this review is to give an overview of reported role of PPB in several therapeutic areas, highlight cases where PPB changes are clinically relevant, and provide drug metabolism and pharmacokinetics recommendations in discovery and development settings. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2953–2994, 2013